Hubungan Antara Kemandirian Belajar dengan Prestasi Belajar PAI Siswa Kelas III SDN Panularan Surakarta - Miftaqul al Fatihah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
The background of this research werethe less satisfying result of the student achievements in PAI; the lack of students seriousness to plan their learning activities;and the lack of responsibility for addressing the problems of their studies. The purpose of this research was to find out: 1) the students’ learning independence 2) the PAI learning achievement, and 3) the relationship between students’ learning independence and PAI achievements of grade III students in SDN Panularan Surakarta academic year 2015/2016. This research employed correlational quantitative approach. It was carried out from May 2015 until June 2016 with a total sample of 33 students. Samples were determined using simple random sampling, and data were collected using questionnaireand test. There were only 30 out of 40 questions in the questionnaire and 26 out of 27 questions in the test declared as valid and reliable after thetrial. Hypothesis testing is performed with acorrelation of product moment. This study concluded that the students’ learning independence was categorized as moderate (64.7%) so was their PAI learning achievement (16.95%). It was also found that students’ learning independence and their achievement are positively correlated.Keywords: Study independence, PAI learning achievement, correlation of product moment.